Knowledge and attitude of postnatal mothers towards Human Breast Milk Banking in a selected Hospital - Lavina Rodrigues; Ashi Abraham; Ashlin Jeniciya D’ Almeida; Anit Shaju; Anjali Jose; Anjana Babu (International Journal of Midwifery Nursing And Practices, 2023)
Background: Breast milk is universally endorsed as unique, innate and vital feed, gifted by nature for neonates. Human Breast milk banks function as stockpile for women who are incapable to provide their own breast milk to their unwell or confined infants. In Indian scenario, donation of breast milk is an emerging notion and has been introduced among few metropolises across the nation. Unavailability to breastmilk foster infants more susceptible to morbidity and mortality. Hence, postnatal women must aim to contribute their breast milk in this endure to save lives worldwide. Aim: The objective is to evaluate postnatal mothers' understanding and disposition regarding the concept of Human Breast Milk Banking.Materials & Methods: A cross sectional correlational research design with purposive sampling technique was adopted to select 50 postnatal mothers for the study. Demographic proforma, structured knowledge questionnaire and attitude scale on Human Breast Milk Banking were the tools used to collect the data. Results: The findings showed that, 70% of the postnatal mothers had good knowledge and 8% had average knowledge as well as 78% had favourable attitude and 22% had neutral attitude towards human breast milk banking. The ‘r’ value was computed and found a significant positive correlation of postnatal mothers towards human breast milk banking (r=0.217, p>0.05). Conclusion: The findings suggested that parents need to be educated about the benefits of human breast milk banks is very much indispensable to provide nourishment to the infants also the choice and decision making among the parents in selecting an excellent feeding plan for their sick neonates.
Keywords: Knowledge; attitude; human breast milk banking; infant feeding; postnatal mothers